2020
DOI: 10.1111/acem.13908
|View full text |Cite
|
Sign up to set email alerts
|

Provider Perspectives on the Use of Evidence‐based Risk Stratification Tools in the Evaluation of Pulmonary Embolism: A Qualitative Study

Abstract: Objectives Providers often pursue imaging in patients at low risk of pulmonary embolism (PE), resulting in imaging yields <10% and false‐positive imaging rates of 10% to 25%. Attempts to curb overtesting have had only modest success and no interventions have used implementation science frameworks. The objective of this study was to identify barriers and facilitators to the adoption of evidence‐based diagnostic testing for PE. Methods We conducted semistructured interviews with a purposeful sample of providers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 36 publications
(78 reference statements)
0
19
0
Order By: Relevance
“…Although qualitative studies have explored clinician attitudes toward SDM in general 23 and toward the use of evidence‐based risk‐stratification tools, 24 our study is the first to specifically explore the implementation of DAs to facilitate SDM in the ED setting. SDM has been lauded as a method to deliver high‐quality, patient‐centered care in the ED, 1 , 2 , 25 and DAs have been identified as a means to facilitate and standardize the delivery of SDM.…”
Section: Discussionmentioning
confidence: 99%
“…Although qualitative studies have explored clinician attitudes toward SDM in general 23 and toward the use of evidence‐based risk‐stratification tools, 24 our study is the first to specifically explore the implementation of DAs to facilitate SDM in the ED setting. SDM has been lauded as a method to deliver high‐quality, patient‐centered care in the ED, 1 , 2 , 25 and DAs have been identified as a means to facilitate and standardize the delivery of SDM.…”
Section: Discussionmentioning
confidence: 99%
“…62 receive diagnostic imaging to assess for PE. [63][64][65][66] Of note, both the PERC derivation and validation cohorts were approximately twothirds women. Sex was evaluated in the derivation study but was not found to be significant and therefore is not included in the decision tool.…”
Section: Clinical Evaluation and Diagnosismentioning
confidence: 99%
“…Key barriers included uncertainty around when and how to apply the CSRS recommendations, lack of resources (e.g., cardiac monitors), lack of buy-in from the broader medical team, discomfort (hesitancy) using CSRS, and lack of evidence about the impact on patient outcomes. Surprisingly, no reference on workload or time constraint was brought up, as is often found in other studies (39)(40)(41)(42). Our ndings suggest that physician capability should be a central target of implementation supports, speci cally the capability to interpret CSRSbased criteria and apply it across a range of clinical presentations.…”
Section: Discussionmentioning
confidence: 63%
“…In our study, participants largely referred to educational meetings (e.g., combined grand rounds inclusive of all relevant specialities) and educational videos. Skill-building can be supplemented by creating increased opportunity to utilize the CSRS, including integration into the EMR, engaging local champions, displaying posters, and sending e-mail communications to encourage use (41,42,46). This suite of strategies are commonly used in the ED setting (46) and have demonstrated effectiveness in promoting guideline-adherent care (47).…”
Section: Discussionmentioning
confidence: 99%